Prognosis and risk factors of patients with upper urinary tract urothelial carcinoma and postoperative recurrence of bladder cancer in central China - Wang, Qingwei; Zhang, Tao; Wu, Junwei; Wen, Jianguo; Tao, Deshang; Wan, Tingxiang; Zhu, Wen (BMC urology, 2019)
To investigate the prognostic risk factors and postoperative recurrence of bladder cancer in patients with upper urinary tract urothelial carcinomas (UTUCs). Data of 439 UTUC patients were retrospectively analyzed. Follow-up and analysis of smoking effects, consumption of traditional Chinese medicine containing aristolochic acid, history of bladder cancer, age, sex, presence or absence of diabetes mellitus (DM), metformin use, tumor characteristics (number, location, stage, grade), and open or laparoscopic surgery on the prognosis of UTUCs were performed. Cox proportional hazard regression analysis was performed to analyze the relationship between various factors and the postoperative survival rate. The survival rate was analyzed using the Kaplan-Meier method. Moreover, logistic regression analysis was performed to analyze the relationship between the above mentioned factors and postoperative recurrence of bladder cancer. Overall, 439 patients met, including 236 males (53.7%) and 203 females (46.3%), the criteria for the final statistical analysis, and the average age was 66.7 years. The 1-, 3-, and 5-year overall survival rates of 439 UTUC patients were 90.0, 76.4, and 67.7%, respectively. The 5-year survival rates of T1, T2, T3, and T4 patients were 90.2%, 78%, 43.8%, and 18.5%, respectively. Factors influencing the long-term survival rate of UTUC patients were smoking, taking traditional Chinese medicine containing aristolochic acid, history of bladder cancer, age, tumor size, tumor stage, tumor grade, and lymph node metastasis. The risk factors related to postoperative bladder cancer recurrence were advanced tumor stage, high grade tumor, preoperative ureteroscopy, ureteral urothelial carcinoma, no postoperative bladder perfusion chemotherapy and DM without metformin use. Advanced tumor stage and presence of a high-grade tumor were risk factors for not only poor UTUC prognosis but also BC recurrence. In addition, preoperative ureteroscopy, ureteral urothelial carcinoma and DM without metformin use were high risk factors for BC recurrence, whereas regular postoperative bladder perfusion chemotherapy was a protective factor.